Signs of Alveolar Collapse in Idiopathic Pulmonary Fibrosis, Hypersensitivity Pneumonitis and Systemic Sclerosis Revealed by Inspiration and Expiration Computed Tomography - Marco Fabian Wittwer; Soung-Yung Kim; Alexander Leichtle; Sabina Berezowska; Sabina A. Guler; Thomas Geiser; Johannes Heverhagen; Britta Maurer; Alexander Poellinger (BioMed, 2023)
Idiopathic pulmonary fibrosis (IPF), hypersensitivity pneumonitis (HP) and systemic sclerosis (SSc) are among the most common entities that cause pulmonary fibrosis. Alveolar collapse with subsequent collapse induration of lung tissue is thought to contribute to the fibrotic transformation. The purpose of this study was to examine lung tissue in computed tomography (CT) of non-diseased appearance during expiration for signs of increased density suggesting collapsibility in fibrosing lung diseases. We further analyzed the diaphragmatic movements during the respiratory cycle to determine relationships between density differences and the apex–diaphragm diameter. Significant differences in attenuation changes between inspiration and expiration of unaffected lung parenchyma were detected between IPF and controls and between HP and controls for all lung lobes (p < 0.001). Only minor differences were found between SSc and controls. There was no clinically relevant difference between patients with IPF and those with HP. The measured absolute apex–diaphragm diameter in inspiration and expiration demonstrated a statistically significant difference between patients with IPF versus normal controls. However, the diaphragmatic excursions were not different between these groups. Compared to controls, CT lung density increases significantly more during expiration in the fibrotic lungs of IPF and HP patients. The observed increase in density might indicate the collapse of alveoli during expiration and may represent a common pathophysiologic feature of fibrosing lung diseases. The density changes and lung extensions do not have the same ratios across different diseases and controls.